2011
DOI: 10.1007/s00394-011-0286-0
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio, waist circumference, and body mass index as indices of cardiometabolic risk among 36,642 Taiwanese adults

Abstract: PurposeWe aimed to investigate the association of body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) with cardiometabolic risk.MethodsIn this cross-sectional study, 21,038 men and 15,604 women who participated in a health check-up were included.ResultsIn both men and women, the area under the curve (AUC) of WHtR was significantly greater than that of BMI or WC in the prediction of diabetes, hypertension, high total cholesterol, high triglycerides, and low HDL-cholesterol (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
126
3
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 38 publications
14
126
3
21
Order By: Relevance
“…23 In the present study also, it was found that individuals who were normal and overweight according to BMI, found to be obese according to WHtR greater than 0.5.…”
Section: Discussionsupporting
confidence: 69%
“…23 In the present study also, it was found that individuals who were normal and overweight according to BMI, found to be obese according to WHtR greater than 0.5.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, a previous study reported the superiority of the waist-to-height ratio as an anthropometric index to evaluate clustering of coronary risk factors among nonobese men and women, compared with waist circumference (Hsieh and Muto 2005). Among Taiwanese adults, persons of either sex with a normal BMI or waist circumference, but with an elevated waist-to-height ratio, had higher of various cardio-metabolic risk factors (Li et al 2011). Thus, even among non-obese women, low birth weight infants with a higher adult waist-to-height ratio might have an increased risk of cardiovascular disaese.…”
Section: Discussionmentioning
confidence: 99%
“…Among Taiwanese adults, a waist-to-height ratio greater than 0.5 is a simple, yet effective indicator of centralized obesity and associated cardio-metabolic risk, even among individuals deemed 'healthy' according to BMI and WC (Li et al, 2013). Recent systemic review and meta-analysis also demonstrate that waist-to-height ratio is a better screening tool than WC and BMI in predicting cardio-metabolic risk (Ashwell et al, 2012).…”
Section: A New Index Of Abdominal Obesity Which Effectively Predicts mentioning
confidence: 99%